TRANSAKSI E-COMMERCE DALAM PERSPEKTIF MAQASHID SYARIAH - Nuning Nurna Dewi; Achmad Fathoni Rodli; Relita Rofiqoh; Maslahatus Saidah; Maris Wahidatul ‘Ailah (Ecopreneur.12, 2022)
E-Commerce is a trade or transaction that uses electronic media such as the internet, where its use is more efficient, practical and can reach various regions and even various countries, with the convenience offered making many consumers prefer to make buying and selling transactions using e-commerce. This can be seen based on the results of revenue, obtained from the 2019 e-commerce statistics body as many as 45.30 e-commerce businesses in Indonesia that began using the internet in 2017-2018, while in 2019 as much as 25.11%. The purpose of this study is to find out how e-commerce transactions can be seen from the sharia maqashid. This type of research uses a library research approach, the source of which is obtained through books, journals and e-commerce statistical data related to this research. The results of the study show that e-commerce transactions are in accordance with the 5 (five) principles of sharia maqashid, namely: Hifdzu din (protecting religion), Hifdzu nafs (protecting souls), Hifdzu aql (protecting thoughts), Hifdzu mal (protecting assets), Hifdzu nasab (protect offspring) so that it can obtain a general benefit, benefit from the buyer's side such as making transactions easier, and benefits from the seller's side because it is more cost-effective, while from the community side provides new employment or business. The Islamic law of transactions using e-commerce is permissible based on the principle of mashlahah because human needs for technological advances are increasingly important by trying to improve and avoid technical weaknesses and sharia balance, because it cannot be denied that the mechanisms created by humans are not immune from weaknesses However, as long as it is still relatively safe and supported by proper security measures, it will create a problem for its users.